Tipping the scale: Effects of physical activity and body composition on cardiac parameters in postmenopausal females - Mads Fischer; Andrea Tamariz‐Ellemann; Jon Egelund; Nicolai Rytter; Ylva Hellsten; Lasse Gliemann (Physiological Reports)
Abstract The risk of cardiovascular disease increases significantly after menopause. We sought to assess the impact of different activity levels on cardiac structure and function in postmenopausal women. We grouped age‐similar, postmenopausal women by self‐reported physical activity levels over two decades. The study involved 34 women (age 61 ± 1 years; 11 ± 2 postmenopausal years; body mass index 23 ± 3 kg/m2) categorized into three activity tiers: sedentary (SED; ≤1 h exercise weekly; n = 9); moderately active (MOD; ≥2 ≤6 h low/moderate intensity exercise weekly; n = 11) and highly active (HIGH; >4 h of moderate/high intensity exercise weekly; n = 14). Maximum oxygen uptake (VO2max) differed significantly (p < 0.05) between the groups (24.9 ± 5.8; 30.5 ± 5.8; 38.4 ± 4.4 mL O2/kg/min; SED, MOD and HIGH respectively). Conversely, there were no differences (p > 0.05) in height, Total fat‐free mass, body surface area or in echocardiographic measures of left ventricular (LV) morphology, systolic function, diastolic function and right ventricular function. Contrary to our hypothesis, these findings reveal that marked differences in activity level and VO2max are not reflected in measures of LV morphology or echocardiographic indicators of cardiac diastolic or systolic function in postmenopausal women of similar body size.